132 Clinical Efficiency of Combination Therapy Using Testosterone Replacement Therapy, Phosphodiesterase 5 Inhibitors and Kampo Herbal Medicine for Eugonadal Patients with Late-Onset Hypogonadism Syndrome. (1st May 2022) - Takeuchi, H; Okubo, H; Komatsu, N
ABSTRACT: Introduction: Late-onset hypogonadism (LOH) syndrome is an endocrine disorder that is characterized by low levels of androgen and a subsequent decline in various physical functions. Regarding the treatment of LOH syndrome, the use of several agents, primarily testosterone replacement therapy (TRT), has been reported. In addition to TRT, certain therapies for LOH syndrome commonly include counseling, antidepressants, PDE5i and herbal medicine (Kampo). Objective: In the present study, the effectiveness of initial treatment by combination therapy using TRT, herbal medicine and PDE5i in male patients with LOH were determined. The patients' clinical background, changes in symptom scores and clinical parameters were analyzed to verify the effectiveness of the treatment intervention. Methods: Between April 2017 and September 2018, 21 patients with LOH-associated symptoms, including chief complaints of decreased libido, ED, depression and general fatigue, visited the menopausal outpatient clinic. At their first visit, the patients were evaluated by reviewing their medical history, a physical examination and detection of clinical parameters, and their general LOH symptoms were judged according to Heinemann's Ageing Males' Symptoms (AMS) scale. Voiding function was evaluated by the International Prostate Symptom Score (IPSS) and sexual function was evaluated by the International Index of Erectile Function-5 (IIEF-5) score. Blood screening, including hemoglobin (Hb), aspartate transaminase, alanine transaminase, creatinine, total cholesterol (T-Cho), triglyceride, blood sugar and PSA, and endocrinological variables including FT, LH and FSH were determined prior to monitoring endocrinological variables for any treatment of LOH. TRT or an oral treatment, such as herbal medicines or PDE5i, was provided for each symptom. For the TRT, T enanthate was administered via intramuscular injection every four weeks for a total of 12 weeks or testosterone ointment was applied. The most appropriate herbal medicine was administered to the patients according to their pathogenic alterations. A total of three traditional Japanese herbal medicines were candidates for LOH treatment in the present study. Total of 21 patients were enrolled and after 12 weeks, the clinical efficacy was evaluated based on improvement of LOH symptoms via same laboratory parameters and questionnaires. Results: The overall AMS scores, as well as the psychological, physical and sexual AMS factors prior to and after treatment in the TRT, testosterone enanthate (T enanthate) monotherapy and T enanthate + PDE5i treatment groups were significantly improved. In the herbal medicine group, only the AMS physiological factors were significantly improved after treatment compared with the baseline. The improvement of the overall AMS scores, as well as the physiological and sexual AMS factors, were significantly negatively correlated with the free testosterone (FT) value prior to treatment. Conclusions: Treatment with combination therapy using TRT, herbal medicine and PDE5i improved AMS scores in patients with LOH syndrome. Particularly in patients with LOH syndrome and low FT, the symptoms were significantly improved following combination therapy. Disclosure: Work supported by industry: no.